P-drug selection: Choosing medicines objectively - Shankar, Ravi P (Nepal Journal of Epidemiology, 2013)
I read with great interest the article by Banerjee I. about ‘Concepts of P drug selection’ in the current issue of the Nepal Journal of Epidemiology. Personal (P) drug selection is an excellent exercise to teach students to prescribe medicines based on objective criteria and unbiased sources of medicine information. I had been involved in initiating the exercise on P drug selection at Manipal College of Medical Sciences, Pokhara. I had also been involved with the exercise at KIST Medical College, Lalitpur. Recently I have started this exercise at the Xavier University School of Medicine at Aruba, Dutch Caribbean. DOI: http://doi.dx.org/10.3126/nje.v3i2.8510